Efeito do desbaste seletivo nas estimativas de parâmetros genéticos em progénies de Pinus caribaea Morelet var. hondurensis - Moraes, Mario Luiz Teixeira de [UNESP]; Missio, Robson Fernando; Silva, Alexandre Marques da [UNESP]; Cambuim, José [UNESP]; Santos, Luiz António dos; Resende, Marcos Deon Vilela de (My University, 2007)
The objective of this work was to study the effect of selective thinning on the estimates of genetic parameters in progenies of Pinus caribaea var. hondurensis. The progeny test was installed in June 1986, following a 10 × 10, triple square lattice design, containing ten trees in linear plots in 3.0 × 3.0m spacing. Twelve years after the planting, a selective thinning based on Multi-effect index (selection for DBH) was performed, leaving six trees per plot. The assessments were done in four situations: A (before thinning); B (among thinned trees); C (among remnant trees at 13 years of age) and D (two years after the thinning). The following traits were analyzed: total height (H), diameter at breast height (DBH), volume (VOL), stem form (FOR), foxtail (FT), wood density at 1.3 m (WD1) and wood density at the half height (WD2). The thinning led to increase in the estimates of variability among progenies for VOL and decrease for ALT and DBH. There was a high and positive genetic correlation among the growth traits, mainly between DBH and VOL. The latter remained unchanged after thinning. The narrow-sense heritabilities at the individual level, showed a slight increase while at the family mean level had a reduction with the thinning. The estimates of breeding values increased with the thinning. This may lead to an easier identification of the best progenies in further selection.
Effect of selective thinning on the genetic parameters estimates in Pinus caribaea Morelet var. hondurensis progenies
Keywords: Genetic variability; Progeny test; Tree improvement; Multi-effect index; Parameter estimation; Genetic engineering; Breeding; Genetic Engineering; Thinning